Foundations of incidence geometry projective and polar spaces - Ueberberg, Johannes; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Incidence geometry is a central part of modern mathematics that has an impressive tradition. The main topics of incidence geometry are projective and affine geometry and, in more recent times, the theory of buildings and polar spaces. Embedded into the modern view of diagram geometry, projective and affine geometry including the fundamental theorems, polar geometry including the Theorem of Buekenhout-Shult and the classification of quadratic sets are presented in this volume. Incidence geometry is developed along the lines of the fascinating work of Jacques Tits and Francis Buekenhout. The book is a clear and comprehensible introduction into a wonderful piece of mathematics. More than 200 figures make even complicated proofs accessible to the reader.
I Projective and Affine Geometries -- 1. Introduction -- 2. Geometries and Pregeometries -- 3. Projective and Affine Planes -- 4. Projective Spaces -- 5. Affine Spaces -- 6. A Characterization of Affine Spaces -- 7. Residues and Diagrams -- 8. Finite geometries -- II Isomorphisms and Collineations -- 1. Introduction -- 2. Morphisms -- 3. Projections -- 4. Collineations of projective and affine spaces -- 5. Central Collineations -- 6. The Theorem of Desargues -- III Projective Geometry over a Vector Space -- 1. Introduction -- 2. The Projective Space P(V) -- 3. Homogeneous Coordinates of Projective Spaces -- 4. Automorphisms of P(V) -- 5. The Affine Space AG(W) -- 6. Automorphisms of A(W) -- 7. The First Fundamental Theorem -- 8. The Second Fundamental Theorem -- IV Polar Spaces and Polarities -- 1. Introduction -- 2. The Theorem of Buekenhout-Shult -- 3. The diagram of a polar space -- 4. Polarities -- 5. Sesquilinear Forms -- 6. Pseudo-quadrics -- 7. The Kleinian Polar Space -- 8. The Theorem of Buekenhout and Parmentier -- V Quadrics and Quadratic Sets -- 1. Introduction -- 2. Quadratic Sets -- 3. Quadrics -- 4. Quadratic Sets in PG(3, K) -- 5. Perspective Quadratic Sets -- 6. Classification of the Quadratic Sets -- 7. The Kleinian Quadric -- 8. The Theorem of Segre -- 9. Further Reading -- References -- Index.
Electronic reproduction.
Keywords: Geometry, Modern; Electronic books